Literariness and Racial Consciousness in Paule Marshall’s Memoir Triangular Road and Gloria Naylor’s Fictionalized Memoir 1996 - Łobodziec, Agnieszka (Studia Anglica Posnaniensia, 2016)
Black American women writers were side-lined by the literary canon as recently as the 1980s. Today, as a result of their agency, a distinct literary tradition that bears witness to black women’s particular expressiveness is recognized. Bernard Bell observes that the defining features common to most literary works by black American women are a focus on racist oppression, black female protagonists, the pursuit of demarginalization, women’s bonding, women’s relationship with the community, the power of emotions, and black female language. Although these elements refer predominantly to novels, they are also present in Paule Marshall’s memoir Triangular Road (2009) and Gloria Naylor’s fictionalized memoir 1996 (2005). Moreover, the two works are fitting examples of racial art, the point of departure of which, according to Black Arts Movement advocates, should be the black experience. Actually, since through memoirs the authors offer significant insights into themselves, the genre seems closer to this objective of racial art than novels. At the same time, taking into consideration the intricate plot structures, vivid images, and emotional intensity, their memoirs evidence the quality of literariness i.e., in formalist terms, the set of features that distinguish texts from non-literary ones, for instance, reports, articles, text books, and encyclopaedic biographical entries. Moreover, Marshall and Naylor utilize creative imagination incorporating fabulation, stories within stories, and people or events they have never personally encountered, which dramatizes and intensifies the experiences they relate. In Marshall’s memoir, the fictitious elements are discernable when she imagines the historical past. Naylor demarks imagined narrative passages with separate sections that intertwine with those based upon her actual life experience.